Characterization of the novel HLA‐B*18:161 allele by sequencing‐based typing. (22nd June 2020) - Elsermans, Vincent; Visentin, Jonathan; Top, Isabelle; Varlet, Pauline; Labalette, Myriam
Abstract : HLA‐B*18:161 differs from HLA‐B*18:01:01:01 by one nucleotide substitution in codon 136 in exon 3.